Development of Technology Tools in Next-Generation Learning Spaces (NGLS) Framework: A Fuzzy Delphi Analysis - Sanu raJaya; Rozniza Zaharudin; Muhammad Nidzam Yaakob (International Journal of Educational Excellence and Innovation, 2024)
Malaysia education has embarked on its digitalization journey and the Malaysia Digital Economy Blueprint is formulated as the action plan. To reform the initiative with a focus toward change in teaching and learning with technology integration. This article aims to design and develop Next Generation Learning Spaces (NGLS) conceptualize framework in technology tools using Fuzzy Delphi (FDM) method. Therefore, this research study aims to obtain experts consensus from 13 experts about the construct and the elements of technology tools in the framework. An instrument that involves 7 elements of technology hardware, 4 elements of using technology for homework, 4 elements for test and quizzes, 5 elements for codingandprogramming,4elementsof onlinetutorialand5elementsofonlinelearning. The findings illustrated are mostly agreed by the experts with all the elements of the technology that suggested in the framework. The threshold value for accepted elements is between 0.000 to 0.183 which is the acceptable elements that must be lower than (d ≤ 0.2). From the FDM analysis, it is also indicated the expert consensus percentages value in range between 75 % to 100 %, which is shown the acceptable percentage value more than 75% as required by FDM requirement. The third requirement in FDM is the value of alpha cut which is the value of α- cut ≥ 0.5. In term of technology tools, all the elements illustrated that value of alpha cut is higher than 0.5. Thus, mostly the acceptable elements have the qualified of alpha cut value between 0.874 to 1.000. Therefore, the defuzzification process will shift to ranking all the technologytools elements in the framework based on experts’ consensus. This research study definitely come out with a list of technology tools in NGLS conceptualize framework.